Livestock based Integrated Farming System - Gupta, Gaurendra; Palsaniya, D R; S, Manjangouda S; Upadhyay, Deepak; Suman, Manju; Chand, Khem (Indian Farming, 2020)
The Indian economy is predominantly agriculture oriented and livestock rearing forms an integral part of rural living. Livestock is important part of agriculture diversification and income enhancement, and crucial for nutrition enhancement. The modern and high input agriculture, along with providing many advantages, also created some problems such as, replacement of system approach with component approach which dismantled the balance between agriculture and livestock and created a big gap between animal feed requirement and availability. Despite the enormous contribution to the national economy and remarkable growth in milk production in last few decades, the productivity of our animals is low due to improper nutrition, health care and management. The availability of quality feed and fodder is one of the main reasons for poor performance of livestock. The present availability of feeds in the country is estimated to be only 40% of the total requirement of these animals. National commission of agriculture came up with a recommendation that a minimum 10% of the net arable area in the country should be under improved forage crops to meet the forage needs of the livestock population. However, it is estimated that the area under forage crops is about 5.23% only, leaving a wide gap between supply and demand. One of the major constraints for less availability of fodder is ‘component approach’ of modern agriculture where commercial and monoculture farming practices are replacing traditional fodder production areas gradually. Hence, it is the need of hour to adopt such farming practices which are based on system approach. Integrated farming system (IFS) is one of the system based approach which enables the farmers to devote some part of land for fodder crops along with the food and horticultural crops.